Applying a macro-finance yield curve to UK quantitative easing - Jagjit S. Chadha; Alex Waters (University of Kent, School of Economics, 2014)
We estimate a macro-finance yield curve model for both the nominal and real forward curve for the UK from 1993 to 2008. Our model is able to accommodate a number of key macroeconomic variables and allows us to estimate the instantaneous response of the yield curve and so gauge the impact of Quantitative Easing on forward rates. We find that 10 year nominal interest rates on average are lower by 46 basis points which can largely be explained by three main channels: portfolio balance; liquidity premium and signalling but there is no sizeable impact on real interest rates.
Keywords: E43; E44; E47; E58; E65; 330; Term Structure of Interest Rates; Monetary Policy; Quantitative Easing